Analytical methods applied for ozone gas detection: A review - Petruci, João Flávio da Silveira; Barreto, Diandra Nunes; Dias, Mariana A.; Felix, Erika P.; Cardoso, Arnaldo A. [UNESP] (Elsevier, 2022)
Ground-level ozone has been increasing worldwide, mainly due to the high anthropogenic emissions of NOx and VOCs. In addition, ozone generators are sold as water and air purifiers, and are also used to assist in decontaminating spaces with odors or chemical/biological hazards. The amount of ozone released in a small area may exceed public health standards, compromising indoor air quality. Long-term exposure to ozone can potentially cause harmful health effects such as respiratory illness and decreased lung function, as well as damage to materials and vegetation. Therefore, ozone monitoring and control policies are essential for preserving outdoor and indoor air quality. The determination of ozone gas is still a challenge for modern analytical chemistry, due to its wide concentration range (low ppb to low ppm), short-term fluctuations, and high reactivity, together with the difficulty in preparing reliable standard solutions. Advances in various ozone measurement techniques have been published over the last ten years. The methods for monitoring ozone aim to combine qualities such as real-time measurement, low cost, portability, miniaturization, detection of a wide concentration range, and analytical reliability. However, techniques with high applicability need to be further explored in terms of device construction and components active towards ozone. This review provides a critical discussion of the most widely used techniques employed for gaseous ozone monitoring in the last ten years and the recent progress in this area. Future challenges and perspectives in developing trace gas sensors are also considered.
Keywords: Air quality; Gas sensing; Metal oxide sensors; Optical sensors; Ozone